Serum neurofilament light chain levels at attack predict post-attack disability worsening and are mitigated by inebilizumab: analysis of four potential biomarkers in neuromyelitis optica spectrum disorder - Aktas, Orhan; Hartung, Hans-Peter; Smith, Michael A; Rees, William A; Fujihara, Kazuo; Paul, Friedemann; Marignier, Romain; Bennett, Jeffrey L; Kim, Ho Jin; Weinshenker, Brian G; Pittock, Sean J; Wingerchuk, Dean M; et al. (Journal of Neurology, Neurosurgery & Psychiatry, 2023)
ObjectiveTo investigate relationships between serum neurofilament light chain (sNfL), ubiquitin C-terminal hydrolase L1 (sUCHL1), tau (sTau) and glial fibrillary acidic protein (sGFAP) levels and disease activity/disability in neuromyelitis optica spectrum disorder (NMOSD), and the effects of inebilizumab on these biomarkers in N-MOmentum.MethodsN-MOmentum randomised participants to receive inebilizumab or placebo with a randomised controlled period (RCP) of 28 weeks and an open-label follow-up period of ≥2 years. The sNfL, sUCHL1, sTau and sGFAP were measured using single-molecule arrays in 1260 scheduled and attack-related samples from N-MOmentum participants (immunoglobulin G (IgG) autoantibodies to aquaporin-4-positive, myelin oligodendrocyte glycoprotein-IgG-positive or double autoantibody-negative) and two control groups (healthy donors and patients with relapsing–remitting multiple sclerosis).ResultsThe concentration of all four biomarkers increased during NMOSD attacks. At attack, sNfL had the strongest correlation with disability worsening during attacks (Spearman R2=0.40; p=0.01) and prediction of disability worsening after attacks (sNfL cut-off 32 pg/mL; area under the curve 0.71 (95% CI 0.51 to 0.89); p=0.02), but only sGFAP predicted upcoming attacks. At RCP end, fewer inebilizumab-treated than placebo-treated participants had sNfL>16 pg/mL (22% vs 45%; OR 0.36 (95% CI 0.17 to 0.76); p=0.004).ConclusionsCompared with sGFAP, sTau and sUCHL1, sNfL at attack was the strongest predictor of disability worsening at attack and follow-up, suggesting a role for identifying participants with NMOSD at risk of limited post-relapse recovery. Treatment with inebilizumab was associated with lower levels of sGFAP and sNfL than placebo.Trial registration number NCT02200770.